Seasonal approach to forecast the suitability of spawning habitats of a temperate small pelagic fish under a high-emission climate change scenario - Lima, André R. A.; Garrido, Susana; Riveiro, Isabel; Rodrigues, Diana; Angélico, Maria M. P.; Gonçalves, Emanuel J.; Peck, Myron A.; Silva, Gonçalo (Frontiers in Marine Science, 2022)
Spawning habitats of cold-water, European small pelagic fishes have shifted poleward in the last three decades coincident with gradual ocean warming. We predicted present-day, season-specific habitat suitability for spawning by European sardine Sardina pichardus in the Atlantic Ocean and Mediterranean and Black Seas, and projected climate-driven changes in suitable areas from 2050-2099 under the IPCC – RCP 8.5 scenario. Sea surface temperature and distance to the coast had the greater influences in spawning habitats, reflecting the temperature- and coastal-dependent spawning of sardines. Chlorophyll-a was the third most important explanatory variable for spawning in winter to summer. Winds were predominantly important during autumn, whilst sea surface salinity was an important driver during spring and summer. Present-day, “hotspots” for spawning were identified in regions of highly productive, salty waters, where SST was between 6 and 18°C from autumn to spring or 16 and 25°C during summer and favourable winds occurred that would retain eggs and larvae closer to the coast (< 250 km). For future scenarios, forecasts indicate that environmental optima for spawning is projected to be in regions where SST varies between 11°C and 18°C from autumn to spring; and between 18°C and 24°C during summer. However, a negative relationship between phytoplankton productivity and habitat suitability induced by warming is likely to occur in the future. Projections suggest that suitable spawning habitats in all seasons will shift to higher latitudes, with a prominent range expansion along the coast of Norway during winter and autumn (> 83%). The total spawning area, however, was projected to contract in the future during spring (-10.5%) and autumn (-4.1%) due to losses of currently suitable areas along the Atlantic African Coast and Mediterranean Sea. Such regions currently support the greatest sardine stocks but climate-driven warming and decreased plankton productivity are projected to make these areas unsuitable for spawning and likely also for sardine fisheries in future.